Pengembangan Dan Pendampingan UMKM ChaCha Kitchen Melalui Re-Branding - Moch. Ridho Illahi; Rafi Athallah Rivai; Luqy Aizzatul Fakhiroh; Ignatius Bramantya Prasetyo Dewa; Desi Puspitasari; G. Oka Warmana (STIKes Ibnu Sina Ajibarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses owned by individuals or groups that aim to grow and develop their business. ChaCha Kitchen is one of the MSMEs in Blitar that has been around for a long time. The problem faced by ChaCha Kitchen is the application of branding which is felt to be ineffective so they feel the need to be re-branded. Assistance and development through product re-branding is carried out in several steps, including changing the logo, product design, creating a website, and registering on the marketplace. The purpose of this research is to help develop MSME businesses digitally and help develop products to make them more attractive. The method used in this service is by observing, interviewing, data analysis, re-branding, and evaluation. The results of this study are ChaCha Kitchen MSMEs, namely Instagram feed updates and also websites that can make it easier for MSMEs to market their products and can increase consumer interest so that income will increase rapidly.